2011
DOI: 10.1152/ajplung.00195.2011
|View full text |Cite
|
Sign up to set email alerts
|

The PPARγ ligand rosiglitazone attenuates hypoxia-induced endothelin signaling in vitro and in vivo

Abstract: Kang BY, Kleinhenz JM, Murphy TC, Hart CM. The PPAR␥ ligand rosiglitazone attenuates hypoxia-induced endothelin signaling in vitro and in vivo. Am J Physiol Lung Cell Mol Physiol 301: L881-L891, 2011. First published September 16, 2011 doi:10.1152/ajplung.00195.2011.-Peroxisome proliferatoractivated receptor (PPAR) ␥ activation attenuates hypoxia-induced pulmonary hypertension (PH) in mice. The current study examined the hypothesis that PPAR␥ attenuates hypoxia-induced endothelin-1 (ET-1) signaling to mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 58 publications
4
70
0
Order By: Relevance
“…1), but its down-regulation may induce, rather than repress, EDN1. Specifically, prior reports have indicated that knockdown of PPAR␥ induced both PAEC proliferation and EDN1 up-regulation, whereas forced PPAR␥ expression under hypoxia attenuated these effects, suggesting a link between these factors (13). Given the up-regulation of EDN1 by miR-130/301, we investigated whether this relationship was under the control of the miR-130/301-PPAR␥ axis.…”
Section: The Mir-130/301 Family Depends Critically On Ppar␥ For Contrmentioning
confidence: 89%
See 1 more Smart Citation
“…1), but its down-regulation may induce, rather than repress, EDN1. Specifically, prior reports have indicated that knockdown of PPAR␥ induced both PAEC proliferation and EDN1 up-regulation, whereas forced PPAR␥ expression under hypoxia attenuated these effects, suggesting a link between these factors (13). Given the up-regulation of EDN1 by miR-130/301, we investigated whether this relationship was under the control of the miR-130/301-PPAR␥ axis.…”
Section: The Mir-130/301 Family Depends Critically On Ppar␥ For Contrmentioning
confidence: 89%
“…There exists, for example, a great diversity of PPAR␥ function in vascular biology beyond proliferation, from vasoconstriction to metabolism to extracellular matrix deposition (9 -12). In PH, a link has been reported between the vasoconstrictive factor EDN1 and PPAR␥ (13,14), and in turn, EDN1 is known to promote vascular smooth muscle cell contraction and increase vasoconstriction in multiple forms of rodent and human PH (3,(15)(16)(17). However, multiple molecular pathways can regulate EDN1 expression (14,18,19) and other effectors of vasomotor tone, and the comprehensive mechanisms by which these actions are coordinated in PH are still undefined.…”
Section: Pulmonary Hypertension (Ph)mentioning
confidence: 99%
“…All experiments were approved by the VAMC Institutional Animal Care and Use Committee. As previously reported (39), male C57BL/6 mice, 8 to 10 weeks of age, were treated with PIO dissolved in methylcellulose (United States Biological, Salem, MA) at 10 mg/kg body weight or with an equivalent volume of methylcellulose alone used as a vehicle control (Veh) by oral gavage. After 24 h, the mice were infected with PAO1 intranasally (40-42) with 10 8 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PPARg attenuates hypoxic increases in proliferative mediators (e.g., ET-1 and nicotinamide adenine dinucleotide phosphate oxidase 4), in part through inhibition of nuclear factor-kB p65 (22,32,44,45). Interestingly, mounting evidence demonstrates that pharmacological activation of PPARg attenuates pulmonary vascular cell proliferation and PH (46), whereas loss of PPARg expression or function is associated with PH (47). Taken together, these findings led us to postulate in the current study that: (1) chronic hemolysis in SCD stimulates loss of PPARg and increased expression of the proliferative mediator, ET-1, which contributes to PH pathogenesis; and (2) targeting PPARg with existing pharmacological ligands may represent a novel therapeutic approach in SCD to attenuate increases in proliferative mediators and SCD-PH pathogenesis.…”
mentioning
confidence: 99%